Geometric imaging of borophene polymorphs with functionalized probes - Xiaolong Liu (Nature Portfolio, 2019)
Borophene, or 2D boron, is highly polymorphic with many predicted lattice arrangements, complicating the identification of its atomic structure. Here, the authors use functionalized-tip scanning probe microscopy to directly resolve the atomic lattice structures of several borophene polymorphs.